(untitled) (International Journal of Engineering and Computer Science, 2017)
Data is a set of values of quantitative variable information. Data deduplication means that the data compression technique for eliminating duplicate copies of repeating data. In the deduplication process, unique types of data, or byte patterns or images, which are identified and stored during a process of analysis Data deduplication is increasingly accepted as a technique to reduce storage costs. In cloud computing system the data deduplication acts as a special role. The Cloud computing is a type of Internet-based computing, that provides shared computer processing that means data to computers and other devices on demand. The example of cloud services are computer networks, servers, storage, applications and in these most commonly using cloud service is data storage. The data are often stored in cloud in an encrypted form. One application of cryptographic splitting is to provide security for cloud computing. However encrypted data introduce new problems arise in cloud data deduplication, which is big data storage and processing. Existing system suffer from security weakness. They cannot flexibly support data access control and revocation. The cloud-based storage example such as Drop box, Google Drive, and Mozy can save on storage costs via deduplication. We make a data will be secure using a user key before he store in to the cloud. But common encryption modes are randomized. People upload personal or confidential data to the data center of a Cloud Service Provider (CSP) but it is do not give fully secure for the data because the data holders may not be always online or available for such a management, which could cause storage delay. And also create the Dekey is secure in terms of the definitions specified in the proposed security model.